Examining the Psychosocial and Academic Factors Predicting Depression and Anxiety Symptomology Across First-Year and Later-Year University Students - Eckberg, Natalie; Pidgeon, Aileen M.; Magyar, Heidi (European Scientific Journal, ESJ, 2017)
University students across the world report higher levels of mental health problems compared to the general population. Past research has focused on investigating mental health problems among first-year university students. However, a paucity of existing research compares the prevalence of mental health problems in first-year university students to students in later year-levels. To address this gap, the current study compared the level of depression and anxiety symptomology experienced by university students (n = 198) from Australia and the United States, across first, second, third, and fourth-year levels. The results found no significant differences in the level of depression and anxiety symptomology between university students from these countries, and no significant differences in the level of depression symptoms across year-levels. However, university students in the secondyear level reported significantly higher levels of anxiety symptoms compared to first, third, and fourth-year levels. The current study assessed the role of stress appraisal, psychosocial, and coping factors as predictors of depression and anxiety symptoms across all year-levels of university students. Hierarchical multiple regressions indicated higher levels of perceived stress and lower levels of perceived social support from family significantly predicted higher levels of depression symptoms. Higher levels of perceived stress and academic avoidance coping, and lower levels of campus connectedness significantly predicted higher levels of anxiety symptoms. Limitations and implications for future research are discussed.